The Correspondence of Jakub Przyłuski - Ryś, Anna (Jakub Przyłuski (1512–1554): Outline of life and literary work against the background of the epoch, 2022)
The article presents the correspondence between Jakub Przyłuski, Stanisław Orzechowski, Marcin Krowicki and Piotr Kmita from the years 1547–1551. The main problems presented in the letters are three issues: the role of Przyłuski as a critic of Orzechowski’s publications, the conflict between Orzechowski and Kmita, and the marriage of Krowicki.